2020
DOI: 10.3389/fgene.2020.00826
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of SGK1 (Serum- and Glucocorticoid-Regulated Kinase 1) in Major Depressive Disorder: Hypothesis and Mechanisms

Abstract: Major depressive disorder (MDD) is a heterogeneous psychiatric disease characterized by persistent low mood, diminished interests, and impaired cognitive and social functions. The multifactorial etiology of MDD is still largely unknown because of the complex genetic and environmental interactions involved. Therefore, no established mechanism can explain all the aspects of the disease. In this light, an extensive research about the pathophysiology of MDD has been carried out. Several pathogenic hypotheses, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 199 publications
(220 reference statements)
1
21
0
Order By: Relevance
“…Noteworthy, analysis of newborn’s cord blood DNA showed significant associations between this score and maternal depression and anxiety [ 287 ]. Likewise, in another study, the serum- and GC-inducible kinase 1 (SGK1), a GC target gene with relevant implications for MDD pathogenesis [ 288 ], was identified as a crucial molecular mediator of GC-dependent neurogenesis impairment in in vitro cultured human NPCs [ 245 ]. Importantly, SGK1 mRNA levels were increased in the peripheral blood of drug-free depressed patients and in the hippocampus of rats that underwent either prenatal stress or UCMS [ 245 ].…”
Section: Mechanisms Of Stress Acting On Neurogenesismentioning
confidence: 99%
“…Noteworthy, analysis of newborn’s cord blood DNA showed significant associations between this score and maternal depression and anxiety [ 287 ]. Likewise, in another study, the serum- and GC-inducible kinase 1 (SGK1), a GC target gene with relevant implications for MDD pathogenesis [ 288 ], was identified as a crucial molecular mediator of GC-dependent neurogenesis impairment in in vitro cultured human NPCs [ 245 ]. Importantly, SGK1 mRNA levels were increased in the peripheral blood of drug-free depressed patients and in the hippocampus of rats that underwent either prenatal stress or UCMS [ 245 ].…”
Section: Mechanisms Of Stress Acting On Neurogenesismentioning
confidence: 99%
“…GR is kept in an inactive state in the cytoplasm, only translocating from the cytoplasm to the nucleus to execute its functions when it binds to glucocorticoid. Impaired signaling via corticosteroid-activated GR leads to impaired negative feedback regulation and partial glucocorticoid resistance appears to be one of the most robust biological abnormalities observed in mood disorders [ 42 ]. FKBP5, an Hsp90 co-chaperone is a negative modulator of GR activity that promotes GR stability and reduces GR sensitivity to glucocorticoid.…”
Section: Discussionmentioning
confidence: 99%
“…Although SGK1 was initially described for its role in regulating sodium transport in renal collecting duct cells [ 15 ], recent studies have provided evidence for a role of SGK1 in stress and glucocorticoid actions on the brain. Compelling data suggests that SGK1 is involved in the GC-induced reduction in the proliferation and differentiation of human hippocampal progenitor cells and that increased SGK1 expression or function is related to the pathogenic stress hypothesis of major depression [ 42 ]. SGK1 mRNA expression has been found to be significantly increased (positive correlation with FKBP mRNA expression) in the peripheral blood of drug-free depressive patients, as well as in the hippocampus of rats subjected to chronic stress [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The raised level of cortisol in the blood will exacerbate depression by impairing brain functions, such as neuronal survival, neuronal excitability, neurogenesis and memory acquisition [144]. Notably, Skupio et al have found that the co-chaperone FK506 binding protein 51 and serum-and glucocorticoid-inducible-kinase-1 proteins increased in the prefrontal cortex, hippocampus and striatum of mice treated with dexamethasone [137], which could regulate GR sensitivity [145], mediate glucocorticoid effects on neuronal function and contribute to major depressive disorder [146].…”
Section: Nervous Systemmentioning
confidence: 99%